2019
DOI: 10.1108/hff-06-2018-0260
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical investigation on turbulent convective heat transfer of nanofluid flow in a square cross-sectioned duct

Abstract: Purpose The purpose of this study is to numerically investigate the heat transfer enhancement by using two different nanofluids flow throughout the square duct under a constant heat flux (500 × 103 W/m2). Design/methodology/approach In numerical computations, ANSYS Fluent code based on the finite volume method was used to solve governing equations by iteratively. Water, Al2O3-water and TiO2-water nanofluids were used for different flow velocities changing 1 m/s to 8 m/s (i.e. Reynolds number varying from 3,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Simply put, a nanofluid is a fluid involving nanometer-sized particles called nanoparticles (Sheikholeslami et al , 2019a). These nanoparticles are generally made of metals, oxides, carbides or CNTs (Hayat et al , 2018; Senay et al , 2019; Khamis et al , 2015). Frequent base fluids consist of water, ethylene glycol and oil which have been used by many researchers (Sheikholeslami et al , 2019b; Akbar, 2015; Sheikholeslami and Zeeshan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Simply put, a nanofluid is a fluid involving nanometer-sized particles called nanoparticles (Sheikholeslami et al , 2019a). These nanoparticles are generally made of metals, oxides, carbides or CNTs (Hayat et al , 2018; Senay et al , 2019; Khamis et al , 2015). Frequent base fluids consist of water, ethylene glycol and oil which have been used by many researchers (Sheikholeslami et al , 2019b; Akbar, 2015; Sheikholeslami and Zeeshan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…However, in addition the geometrical parameters, several parameters were examined by many researchers to enhance the heat transfer rate and these parameters include pipes material, working fluid and porous media. Nanofluids are anemometric particle dispersions (typically less than 100 nm in diameter), called nanoparticles, in a base fluid in order to improve certain properties [25][26][27][28]. The first fluid dispersed by nanoparticles was prepared by Choi and Eastman in 1995 [25].…”
Section: Introductionmentioning
confidence: 99%
“…The first fluid dispersed by nanoparticles was prepared by Choi and Eastman in 1995 [25]. A number of authors have done experimental and theoretical research on improving heat-transfer with nanofluids [26][27][28][29][30][31] and their results have shown that the heat-transfer rate of nanofluids is higher than that of base fluids (pure water). Much is being done about the Al2O3 nanofluid, which is being investigated experimentally by Kim et al [32] on the effect of the nanofluid on the heat-transfer through a circular tube using Al2O3 nanoparticles in a turbulent regime.…”
Section: Introductionmentioning
confidence: 99%